(untitled) (Sociologisk Forskning, 1998)
The journalistic fallacy An expansion of ”media logic” and media strategies in private and public sectors of society is the point of departure for this paper. The power of journalism is a force drawn upon by a wide range of social agents. The question is whether what appears as a victory of journalistic formats and frames of understanding simultaneously is a journalistic defeat. The paper identifies and discusses current aspects of journalistic practice and ideology which might constitute a journalistic fallacy. Among these aspects is the role of the journalist as an impressario of public issues and possible populistic interpretations of this role. Another related aspect is a restricted and vulgar understanding of power involved in a current conception of journalism as ideology. The expansionof a certain service ideology within the mass media and in other domains of public life is also discussed. The journalistic fallacy can be conducted as well by other social agents as by journalists. Implications of this sour victory of journalism is discussed with reference to the Norwegian social philosopher Hans Skjervheim’s writings, especially on the problems of instrumentalism in social life.